PELAKSANAAN KINERJA SATUAN POLISI PAMONG PRAJA DALAM MENEGAKAN PERATURAN DAERAH DI KABUPATEN CIREBON - Sudika Sudika; Urip Giyono; Elya Kusuma Dewi; Multahibun Multahibun (Fakultas Hukum Universitas Muhammadiyah Cirebon, 2020)
In the context of regulation regional enforce, the first element as implementer in field is regional government. In this case the authority is given to the Civil Service Police Unit (Satpol PP). The civil service police unit has the job is help the Regional leader to create a peace and orderly, so that the administration of the wheels of government can run smoothly and people or society can do their activities safely. One of the objectives of Regional Regulations (PERDA) issued by regional governments (PEMDA) is to guarantee legal certainty, create and maintain public order and order. The Civil Service Police is a local government apparatus with the main jobs is enforce of regional regulations, organizing public order and public order. If connected with the performance of the civil service police Organizational of Cirebon district, so the evaluation performance is carried out based on the job that carried out. The purpose of this study is to describe how the performance of the civil service police of Cirebon district in the job of enforce the local regulation base on regional regulation in Cirebon district. Keywords: Performance of police civil service unit, police civil service unit, regional regulation.